Analisis Pengaruh Impor Baju Bekas Terhadap Pengusaha Tekstil Dalam Negeri di Indonesia - Novita Sari Br Siagian; Nazla Annisa Gunawan Sirait; Firli Wardahlia; Khazanah K (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The import of used clothes is a rather complex problem in Indonesia, especially for domestic textile entrepreneurs. The import of used clothes is seen as a threat to the domestic textile industry because it can reduce the competitiveness of domestic textile products. This research was conducted with the following specific objectives: (1) to identify the factors that influence people's decisions to choose to buy imported used clothing products; (2) knowing the impact of imported used clothes on the business of domestic textile entrepreneurs; and (3) provide policy recommendations that can be implemented to reduce the negative impact of used clothing imports for domestic textile entrepreneurs. This research was conducted by means of a literature study. Data collection was carried out by collecting several previous studies to answer the influence of used clothing imports on domestic textile entrepreneurs in Indonesia. The results of the study show that the factors that influence people's decisions to choose to buy imported used clothing products are divided into two, namely internal and external factors. Internal factors, namely those originating from within the individual concerned such as economic or work conditions, attitudes and beliefs, lifestyle and motivation. External factors are factors that come from outside the individual concerned such as environmental, social and cultural conditions, price and product quality. The import of used clothes has an impact on several things, namely (1) on the survival of domestic textile entrepreneurs, (2) on the quality of products of domestic textile entrepreneurs (3) on the competitiveness of domestic textile products and (4) on employment in the textile industry domestic. Based on the research results, the researchers suggest the government to tighten supervision on the import of illegal used clothes and the government can also consider several measures to control the import of used clothes, such as imposing higher import taxes or limiting the import quota of used clothes. Apart from that, it is also necessary to make efforts to increase domestic production of textiles and textile products so that they can compete with imports of used clothes in terms of quality and price. As well as for the Indonesian people it is hoped that they will love domestic products more.Â